Pengembangan Media Google Sites Berbasis Ethno Sains pada Mata Pelajaran IPAS Sekolah Dasar - Aurellia Faradita Putri; Ishmatun Naila; Kunti Dian Ayu Afani (SAP (Susunan Artikel Pendidikan), 2023)
Researchers developed google sites learning media based on ethnoscience in the IPAS subject as an effort to improve the quality of learning implementation to be better at SDN Putat Jaya. This type of research uses Research and Development (R&D), using the ADDIE model which consists of five stages, namely research, design, development, implementation, and evaluation. Data collection techniques in this study used observation, expert verification forms, questionnaires, and validity tests. The verification test was carried out by two verifiers. Based on the results of the research conducted, it can be concluded that this verification test was carried out by two verifiers. from the material expert verifier, 98% is included in the very efficient category. Students' responses to this web-based learning media obtained 93% results and could be classified as very good, while teachers' responses to learning media obtained a percentage value of 94% and could be classified as very good. The effectiveness results after using Google Sites learning media show student learning outcomes and completeness of 85% in the complete category